2019 IEEE International Conference on Pervasive Computing and Communications (PerCom 2019
DOI: 10.1109/percom.2019.8767403
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Detection of Everyday Social Behaviours and Environments from Verbatim Transcripts of Daily Conversations

Abstract: Coding in social sciences is a process that involves the categorisation of qualitative or quantitative data in order to facilitate further analysis. Coding is usually a manual process that involves a lot of effort and time to produce codes with high validity and interrater reliability. Although automated methods for quantitative data analysis are largely used in social sciences, there are only a few attempts at automatically or semiautomatically coding the data collected in qualitative studies. To address this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…As we mentioned at the outset, it is our hope that, as researchers construct their experiences with the method, the collective knowledge around its use will broaden and evolve and will ultimately render what we document here incomplete or outdated. Further, it is likely that computational advances in behavioral signal processing (Narayanan & Georgiou, 2013) will, in the future, render the coding process more efficient (e.g., through automatic identification of sound files that are silent or contain speech) and that some aspects of EAR coding may ultimately become automated (Dubey, Mehl, & Mankodiya, 2016;Yordanova, Demiray, Mehl & Martin, 2019). Until then, we hope that the documentation of what we have learned over two A PRACTICAL GUIDE TO CODING AND PROCESSING EAR DATA 33 decades or EAR research will help save researchers time and frustration and make a highly labor intensive method more accessible.…”
Section: Resultsmentioning
confidence: 99%
“…As we mentioned at the outset, it is our hope that, as researchers construct their experiences with the method, the collective knowledge around its use will broaden and evolve and will ultimately render what we document here incomplete or outdated. Further, it is likely that computational advances in behavioral signal processing (Narayanan & Georgiou, 2013) will, in the future, render the coding process more efficient (e.g., through automatic identification of sound files that are silent or contain speech) and that some aspects of EAR coding may ultimately become automated (Dubey, Mehl, & Mankodiya, 2016;Yordanova, Demiray, Mehl & Martin, 2019). Until then, we hope that the documentation of what we have learned over two A PRACTICAL GUIDE TO CODING AND PROCESSING EAR DATA 33 decades or EAR research will help save researchers time and frustration and make a highly labor intensive method more accessible.…”
Section: Resultsmentioning
confidence: 99%
“…There are recent sources of unstructured data that are gaining importance in health care applications and may benefit dementia prediction. For example, transcripts of daily conversation are used in [26] to identify social behavior (e.g., giving advice, receiving advice, conversation). Another study [27] uses speech samples and MRI data from 32 semantic dementia patients and 10 HC.…”
Section: Data Sourcesmentioning
confidence: 99%
“…A preliminary step in processing free text consists of syntactic transformations such as removing punctuation and stop words [26]. This is followed by a process which identifies features that are representative of the text.…”
Section: Feature Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Yordanova et al [ 24 ] were the first to investigate the applicability of NLP and machine learning methodologies on data from a naturalistic observation study by Demiray et al [ 6 ]; they introduced an NLP pipeline and machine learning routines to automatically code the social behaviors and interactions (eg, talking to a partner or daughter/son, giving advice, receive support, etc) in the transcripts of recorded conversations. As coding is a manual process that involves much effort and time, their results showed that the use of NLP and machine learning automation on transcripts of recorded conversations enabled reliable coding of social behaviors and interactions, reducing effort and time.…”
Section: Introductionmentioning
confidence: 99%